Analisis Produktifitas Teknisi Menggunakan Metode Full Time Equivalent Dan Objective Matrix Di PT Eurokars Surya Utama - Septian, Ardy; Endih Nurhidayat, Asep (Jurnal Teknik Indonesia, 2023)
Introduction: The research in this thesis is motivated by problems in aftersales services at PT Eurokars Surya Utama, namely the accumulation of units in Waiting Bay and the occurrence of time delays exceeding service estimates. The purpose of this study is to analyze the productivity of technicians using the full-time equivalent and objective matrix methods at PT Eurokars surya utama. Method: The research method used in this study is the study of data. For the data analysis method, this study uses the Full Time Equivalent & OMAX method. Results: The results of this study show that all technicians do excessive work or get a fairly high workload from checking to finishing and also low productivity due to lack of labor. This was obtained based on the results of the FTE method, which was more than 1 and was declared overloaded and the OMAX method which showed the productivity result of the HR ratio of 0.008. The result of 0.008 is the lowest result of the 5 ratios processed. Conclusion: It is necessary to evaluate employee performance and apply FTE and OMAX methods as a basis for determining employee workload so as to prevent overload